Swot strategy analysis of SMEs loloh cemcem at UD. Merta Sari - Fitri Yani Panggabean; Desya Sandayanti (Review of Management, Accounting, and Business Studies, 2021)
This study aimed to analyze the SWOT UMKM Loloh Cemcem strategy (Case Study of Loloh Cemcem Ibu Kunil Production by UD. Merta Sari in Penglipuran Village, Bangli Regency). The informants used in this study were selected purposively. Data collection techniques used by researchers are Observation, Interview, and Documentation. The data analysis technique used was a descriptive method. It was used to make a description of the results of the study. The strategy used was UD. Merta Sari is a SO strategy. The result of this study was the strength of UD. Merta Sari products owned were delicious and beneficial to health, easy to find products, had regular customers, and had hygienic production processes. The disadvantages were that the product was not durable, production was still manual, there were no clear job descriptions and the management was still simple, and online marketing was not optimal. Opportunities that could be utilized by UD. Merta Sari was optimizing resellers, strategic production locations, high demand for products, opening branches, and promotion with the open booths. The threats were products in the form of raw materials to make crackers which were difficult to obtain during the dry season, the emergence of similar product businesses, and government regulations related to the use of plastics. It was difficult for looking for alternatives related to the packaging used by UD. Merta Sari.